EFEKTIVITAS PENERAPAN METODE PjBL DENGAN PERANGKAT LUNAK SKETCHUP DALAM MENINGKATKAN HASIL BELAJAR SISWA SMK PADA MATA PELAJARAN APLIB - Halwati Najwa (CV. ADIBA AISHA AMIRA, 2024)
This research examines the effectiveness of implementing the Project Based Learning (PjBL) method using Sketchup software in improving vocational school student learning outcomes in building interior software application (APLIP) subjects. PjBL engages students in real projects, enhancing critical thinking, creativity and collaboration skills. Sketchup, as an intuitive 3D design tool, helps students understand spatial and aesthetic concepts and improves industry-relevant technical skills. This research uses a literature review of articles published in 2020-2024, analyzing 10 of 40 relevant articles. The research results show that the PjBL method with Sketchup improves students' understanding and skills significantly. Obstacles found include limited access to technology, lack of training for teachers, and resistance to changes in learning methods. However, the application of PjBL with Sketchup has proven effective in preparing students to face the needs of modern industry, increasing learning motivation, and producing graduates who are more competitive in the job market. Technological support and ongoing training are needed to overcome these obstacles and maximize the benefits of the PjBL method in vocational education.